2020
DOI: 10.1007/s12298-020-00761-x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar applied fullerol differentially improves salt tolerance in wheat through ion compartmentalization, osmotic adjustments and regulation of enzymatic antioxidants

Abstract: Earlier we reported that seed pre-treatment with PHF promoted early seedling growth and salinity tolerance in wheat. As a way forward, experiments were conducted to investigate whether and to what extent foliar spray of fullerol could influence growth and physio-biochemical responses in salt stressed wheat. In a control experiment, seeds were sown in sand filled pots (500 g) under control and 150 mM NaCl stress. After 15 days, foliar spray of fullerol at 0, 10, 40, 80 and 120 nM concentration was applied and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…However, the negative impact of salinity depends upon the number of climatic conditions, light intensity, plant species and soil conditions (Kamran et al, 2019; Parida & Das, 2005). In addition, a reduction in the plant growth rate and changes in structural composition as a result of high saline environments can lead to an alteration in the photosynthetic machinery, exclusion of ions, osmotic adjustment and nutrient imbalances (Hussain et al, 2016; Shafiq et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the negative impact of salinity depends upon the number of climatic conditions, light intensity, plant species and soil conditions (Kamran et al, 2019; Parida & Das, 2005). In addition, a reduction in the plant growth rate and changes in structural composition as a result of high saline environments can lead to an alteration in the photosynthetic machinery, exclusion of ions, osmotic adjustment and nutrient imbalances (Hussain et al, 2016; Shafiq et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…to maintain cellular homeostasis (Rehman et al, 2019; Zaheer, Ali, Saleem, Imran, et al, 2020). Previously, many researchers concluded that varieties of antioxidants have increased their activities under salt stressed environments in Vigna radiata (Islam et al, 2016), Triticum aestivum (Shafiq et al, 2020), and Plantago ovata (Kala, 2015). Additionally, drought conditions reduce the photosynthetic rates, expansion of leaves, increase stomatal closure, the levels of ROS and early leaf catabiotic, and decrease the translocation within the plant, resulting in overall decreased crop yields (Ahmad et al, 2017; Anjum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unpredictability of environmental conditions and the inability of plants to move in order to avoid unfavorable conditions, a number of abiotic stress factors threaten plant productivity and sustainability [1,2] Salinity is one of the main environmental stressors limiting crop production globally [3], it causes oxidative damages, ion toxicity, and nutrition imbalance [2,[4][5][6]. According to the United Nations (UN) Environment Program (UNEP), worldwide, approximately 50% of agricultural lands are now characterized as saline soils [6].…”
Section: Introductionmentioning
confidence: 99%
“…Plants are well equipped with an effective ROS scavenging defence mechanism that include enzymatic antioxidants such as Ascorbate peroxidase (APX) ,catalase (CAT), superoxide dismutase (SOD) and peroxidase (POD) and some non-enzymatic antioxidants which protect the cellular structures and other macromolecules from damage caused ROS molecules 53 , 54 . We have observed that the hydrogen peroxide (H 2 O 2 ) levels, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%